The Factors, Forms, Causes, Positive and Negative Impacts of the Digital Divide on Educational Practices from Both Educators’ and Learners’ Perspectives: A Systematic Review - Mollah, Shorif (Integrated Science Education Journal, 2026)
Purpose of the study: The infusion of technology into education has transformed teaching and learning worldwide, offering numerous benefits to learners, educators, and institutions. However, unequal access to technological and educational resources has created two distinct groups: the privileged, who enjoy abundant access and benefits, and the deprived, who lack essential tools and opportunities. This disparity constitutes the digital divide, which creates significant negative effects on learning outcomes and equity. Methodology: This systematic literature review investigates three key aspects of the digital divide in education, which are contributing factors, advantages, and negative impacts. A total of 34 studies were analyzed, representing data and perspectives from 40,548 participants across 25 countries spanning five continents. Main Findings: The findings of this study reveal multiple causes of the digital divide in the educational sector, including limited access to technology, poor internet connectivity and digital literacy, lack of educational tools and financial resources, insufficient institutional infrastructure, as well as negative attitudes and poor communication skills. These deficiencies collectively lead to substantial pedagogical, technical, and social consequences. Novelty/Originality of this study: Notable impacts include widened socio-economic disparities, achievement gaps, reduced interaction and engagement, poor knowledge retention, higher dropout rates, weak digital skills, and diminished relationships between teachers and students. Thus, ultimately, the digital divide fosters a persistent negative perception of technology integration, as many learners and educators view technological use as a frustrating challenge rather than an empowering tool.